Gastrointestinal function and quality of life in postoperative patients of pancreatoduodenectomy - Masabanda Celorio, Veronica; Chavez Balanza, Luis Arturo; Martínez Ordaz, José Luis; Rodríguez Negrete, Elda Victoria; Sanchez Reyes, Karina (International Journal of Research in Medical Sciences, 2024)
Pancreaticoduodenectomy (PD) is a complex, high-risk procedure with insufficient data on long-term quality of life and gastrointestinal function. Therefore, it is necessary to determine the level of quality of life and functional outcomes in these patients. In the following study, we present a case series analysis, establishing a direct relationship between post-surgical evolution and its impact on quality of life and gastrointestinal function, using two questionnaires: Short Form 36 and Gastrointestinal Symptom Rating Scale. Out of 15 patients the prevalence of pancreaticoduodenectomy in women was 69%, with a mean age of 53 years. The average follow-up period was 3.47 years. When applying the Short Form 36, they rated their general health at 68.67 points, emotional well-being at 78 points, and social well-being at 73 points. Regarding the Gastrointestinal Symptom Rating Scale, 100% reported pain and indigestion, some experienced gastroesophageal reflux, diarrhea, steatorrhea, and constipation; none of these symptoms limited daily life. Patients undergoing pancreaticoduodenectomy experience changes in their quality of life; likewise, gastrointestinal function alterations are common. Those who survive the underlying pathology and PD have quality of life and gastrointestinal function close to normal values, with improvements possible through symptom treatment, psychological support, social assistance, and physical rehabilitation.